Strategi Collaborative Governance Dalam Pemerintahan - Aziza Bila; Boni Saputra (Jurnal Transformasi Administrasi, 2019)
At this time, the government must have an active role in carrying out tasks, both duties within the institution and duties to serve public. To balance this task, the government must involve stakeholders. Collaborative Governance exists as a new concept so that there is continuity between public institutions (government and related stakeholders). This to assist the government in carrying out its duties. But now, often the governance of cooperation is not right, so that collaboration is not able to achieve goals. The purpose of this study is to find the right strategy for collaborative governance. The right strategy is expected to help the government to overcome problems in collaborative governance. This research uses a qualitative approach with library research strategy. This research explains that there are various kinds of processes in collaborative governance that can be used in solving existing problems. Through collaborative governance, it is expected that there will be a common perception by public institutions and stakeholders in identifying a problem so that it can be solved together. The results of this study found that the existence of a collaborative strategy in government is not seen from the results, but the existence of a model that is not only based on the process alone or the results. The model that was found in this research is expected to be the right solution in finding a collaborative governance solution for a government.